2019
DOI: 10.1002/cyto.b.21782
|View full text |Cite
|
Sign up to set email alerts
|

Single Antibody Detection of T‐Cell Receptor αβ Clonality by Flow Cytometry Rapidly Identifies Mature T‐Cell Neoplasms and Monotypic Small CD8‐Positive Subsets of Uncertain Significance

Abstract: Background: The diagnosis of T-cell neoplasms is often challenging, due to overlapping features with reactive T-cells and limitations of currently available T-cell clonality assays. The description of an antibody specific for one of two mutually exclusive T-cell receptor (TCR) β-chain constant regions (TRBC1) provide an opportunity to facilitate the detection of clonal TCRαβ T-cells based on TRBC-restriction. Methods: Twenty patients with mature T-cell neoplasms and 44 patients without evidence of T-cell neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 30 publications
(29 reference statements)
4
68
2
Order By: Relevance
“…Novikov et al [ 32 ] reported mean TRBC1-positive events and 95% confident intervals for normal total CD4-positive and CD8-positive T-cells in peripheral blood at 44% (36–53%) and 39% (18–61%), respectively. In patients without demonstrable T-cell neoplasia, we found a similar bimodal expression of TRBC1 on CD4-positive and CD8-positive T-cell subsets gated based on distinct immunophenotypic features, with the exception of occasional small CD8-positive T-cell subsets with a unimodal TRBC1 expression pattern [ 33 ]. Further analysis revealed that these small subsets were truly clonal based on TCR-Vβ-restriction [ 31 ] and T-cell gene rearrangement molecular studies [ 33 ], consistent with benign immunodominant clonotypes (see T-CUS section below).…”
Section: Assay Design and Implementation Of Trbc1 For The Detectiomentioning
confidence: 94%
See 2 more Smart Citations
“…Novikov et al [ 32 ] reported mean TRBC1-positive events and 95% confident intervals for normal total CD4-positive and CD8-positive T-cells in peripheral blood at 44% (36–53%) and 39% (18–61%), respectively. In patients without demonstrable T-cell neoplasia, we found a similar bimodal expression of TRBC1 on CD4-positive and CD8-positive T-cell subsets gated based on distinct immunophenotypic features, with the exception of occasional small CD8-positive T-cell subsets with a unimodal TRBC1 expression pattern [ 33 ]. Further analysis revealed that these small subsets were truly clonal based on TCR-Vβ-restriction [ 31 ] and T-cell gene rearrangement molecular studies [ 33 ], consistent with benign immunodominant clonotypes (see T-CUS section below).…”
Section: Assay Design and Implementation Of Trbc1 For The Detectiomentioning
confidence: 94%
“…In patients without demonstrable T-cell neoplasia, we found a similar bimodal expression of TRBC1 on CD4-positive and CD8-positive T-cell subsets gated based on distinct immunophenotypic features, with the exception of occasional small CD8-positive T-cell subsets with a unimodal TRBC1 expression pattern [ 33 ]. Further analysis revealed that these small subsets were truly clonal based on TCR-Vβ-restriction [ 31 ] and T-cell gene rearrangement molecular studies [ 33 ], consistent with benign immunodominant clonotypes (see T-CUS section below). In our extensive experience using TRBC1 within a single-tube comprehensive T-cell panel, we have found that T-cell neoplasms virtually always have distinct immunophenotypic features that largely separate them from background benign T-cells, but that this separation based on routine gating strategies is often imperfect and results in a very skewed rather than a purely unimodal TRBC1 expression pattern.…”
Section: Assay Design and Implementation Of Trbc1 For The Detectiomentioning
confidence: 94%
See 1 more Smart Citation
“…To further improve the specificity of FC in the diagnosis of SS (vs. reactive erythrodermic conditions), the TCR‐Vβ repertoire of CD4+ T cells showing a suspect phenotype can be analyzed using monoclonal antibodies to 24 TCR‐Vβ segments, which cover 70% of the known TCR‐Vβ repertoire: in virtually all cases, this assay will show either restriction of one of these TCR‐Vβ families or will be negative for all tested antibodies, in both cases confirming monoclonality (Gibson et al, 2016; Lima et al, 2003). However, it should be taken into account that the large number of potential Vβ chains makes the TCR‐Vβ repertoire analysis by FC challenging (and expensive) to test these markers in combination with other markers of MF/SS in routine clinical practice; interestingly, recent studies have preliminarily show the potential utility of one single antibody to confirm clonality by FC (an anti‐TCR‐Cβ1 fluorochrome‐conjugated antibody)—in addition to typical panels for identifying MF/SS cells—for diagnosis and monitoring of SS (Novikov et al, 2019; Shi et al, 2020), although the published data with this novel antibody is limited so far, and therefore more studies are needed specifically addressing its value for MF/SS diagnosis.…”
Section: Diagnosis Of Mf and Ss: Role Of Immunophenotypingmentioning
confidence: 99%
“…Vβ repertoire analysis was employed in challenging cases with immunophenotypic aberrancies, in order to confirm clonality. It is noteworthy that Vβ repertoire analysis is costly, and recently an antibody specific for one of two mutually exclusive TCR β‐chain constant regions (TRBC1) has shown promise for a rapid confirmation of clonality in immunophenotypically aberrant T‐cells (Shi et al, 2019). Other antibodies with potential diagnostic utility include CD2, CD5, CD164, CD158k, CD194 (CCR4), CD279 (PD‐1), CD10, CD45RO, and CD38 (Horna et al, 2020).…”
Section: Discussionmentioning
confidence: 99%